Reimagining Climate Change Education As a Panacea to Climate Emergencies - DAMOAH, Benjamin (International Journal of Environmental, Sustainability, and Social Science, 2023)
Climate change education refers to the process of educating people about the causes, effects, and solutions to climate change. It is a critical component of efforts to address the global climate crisis, as it helps individuals understand the need for action and empowers them to make informed decisions in their personal and professional lives. The paper argued that drastic measures are required to reduce climate change threats, which is a visible adversary that demands the same emergency reaction as the COVID-19 pandemic. Education is considered a response to rising worldwide environmental concerns in the twenty-first century. The world's environmental issues necessitate immediate attention to climate change education. This paper is based on the Diffusion of Innovation (DOI) theory lensed with a transformative paradigm. It explores the present inherent global risk to human health and environmental well-being, as well as its implications for future natural disasters. As a result, this paper contends that an innovative approach to addressing the climate change threat through education is necessary. The paper proposed, among other things, a speedy response to climate change challenges through coordinated worldwide support for climate change education for sustainable development and the inclusion of climate change education in all sectors, integrating climate change education across all disciplines, focusing on social justice and equity, engaging with diverse perspectives, and encouraging action and advocacy.